1997
DOI: 10.1111/j.1432-1033.1997.00583.x
|View full text |Cite
|
Sign up to set email alerts
|

Breast Carcinoma Epithelial Cells Express a Very Low‐Density Lipoprotein Receptor Variant Lacking the O‐Linked Glycosylation Domain Encoded by Exon 16, But with Full Binding Activity for Serine Proteinase/Serpin Complexes and Mr‐40000 Receptor‐Associated Protein

Abstract: Very-low density lipoprotein receptor (VLDLR) belongs to the low-density lipoprotein receptor family of endocytosis receptors. It binds a variety of different ligands, including apolipoprotein E, Mr-40 000 receptor-associated-protein (RAP), and some serine proteinase/serpin complexes. We previously demonstrated the occurrence of two forms of VLDLR in SDS/PAGE, migrating with M,. 105000 and M , 130000, respectively [Heegaard, C. W., Simonsen, A. C. W., Oka, K., Kjflller, L., Christensen, A., Madsen, B., 270,. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 49 publications
0
32
0
Order By: Relevance
“…Several candidate TSGs, such as ANKRD15 in renal cell carcinoma (Sarkar et al, 2002) and SMARCA2 in lung cancer (Reisman et al, 2003), were identified as targets for this 9p24.2-24.3 region. Among other genes located within this region, VLDLR has been also reported to be involved in the pathogenesis of GC and other cancers (Martensen et al, 1997;Nakamura et al, 2000;Chen et al, 2005). However, the association between genomic loss or epigenetic silencing of the VLDLR gene and gastric carcinogenesis has not been reported before.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Several candidate TSGs, such as ANKRD15 in renal cell carcinoma (Sarkar et al, 2002) and SMARCA2 in lung cancer (Reisman et al, 2003), were identified as targets for this 9p24.2-24.3 region. Among other genes located within this region, VLDLR has been also reported to be involved in the pathogenesis of GC and other cancers (Martensen et al, 1997;Nakamura et al, 2000;Chen et al, 2005). However, the association between genomic loss or epigenetic silencing of the VLDLR gene and gastric carcinogenesis has not been reported before.…”
Section: Discussionmentioning
confidence: 94%
“…Expression of several possible cancer-related target genes in the homozygous deletion at 9p24.2-24.3 The homozygously deleted region identified in the HSC58 cell line at 9p24.2-24.3 contains some genes, Silencing of VLDLR in gastric cancer H Takada et al which have been reported as cancer-related genes, including VLDLR (Martensen et al, 1997;Nakamura et al, 2000), ANKRD15 (Sarkar et al, 2002) and SMARCA2 (Reisman et al, 2003). Therefore, we next determined expression levels of VLDLR, ANKRD15 and SMARCA2 with other genes within the homozygously deleted region by means of reverse transcription (RT)-PCR in all 32 GC cell lines and in normal stomach.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we confirmed the cancer-specific splicing pattern of the mRNA encoding the very low density lipoprotein receptor, VLDLR. The VLDLR alternative splicing pattern may be due to the epithelial origin of cancer cells (46).…”
Section: Discussionmentioning
confidence: 99%
“…One variation affects exon 16, encoding the O-linked sugar domain. VLDLR-II, lacking the O-linked sugar domain, binds the M r 40,000 receptor-associated protein (RAP) and serine proteinase-serpin complexes with the same affinity as VLDLR-I (25). A second variation affects exon 4, encoding the third (CTR-3) out of the total eight CTRs.…”
mentioning
confidence: 99%